THE INFLUENCE OF COOPERATIVE BANK OUTLETS UPON LOCAL DEVELOPMENT IN THE PODLASKIE VOIVODESHIP IN POLAND - Korzeb Zbigniew; Sembiyeva Lyazzat; Zhagyparova Аida (Scientific Journal of Pedagogy and Economics, 2019)
The objective of the paper is to evaluate whether the presence of cooperative banks stimulates local development in the municipalities of the Podlaskie Voivodeship in Poland. For this purpose, we have studied the relation between the presence of cooperative banks in 118 municipalities of the voivodeship and the dynamics of changes of selected socio-economic factors: total and own revenues of individual municipalities, their number of inhabitants, number of businesses, average monthly pay and the level of unemployment. The analysis covers the period between Poland’s accession into the European Union and the year 2018. Our results do not confirm earlier findings indicating a close connection between the presence of cooperative banks and local development.